Recyclable magnetic Fe3O4@SiO2/β-NaYF4:Yb3+, Tm3+/TiO2 composites with NIR enhanced photocatalytic activity. (November 2018) - Chen, Zhangxu; Fu, Ming-Lai
Graphical abstract: The recyclable magnetic Fe3 O4 @SiO2/ β-NaYF4 :Yb 3+, Tm 3+ /TiO2 composites were fabricated successfully and was proposed for application in the treatment of contaminated water. Herein, the photodegradation rates reach 76.62%, 68.48%, 30.05% and 27.16% for methylene blue, rhodamine B, methyl orange and phenol under irradiation of 980 nm laser, respectively. Highlights: Fe3 O4 @SiO2 /β-NaYF4 :Yb 3+, Tm 3+ /TiO2 composites have been successfully fabricated. The upconversion of energy transfer from β-NaYF4 :Yb 3+, Tm 3+ to TiO2 was confirmed. Fe3 O4 @SiO2 /β-NaYF4 :Yb 3+, Tm 3+ /TiO2 composites exhibit photocatalytic activity in NIR. The composites can be easily magnetic separated from water after application. The composites show good stability indicated from four recycled tests. Abstract: To extend the activities of TiO2 to the near infrared (NIR) region and to separate and recycle photocatalysts easily is vital for the high harvest of solar energy for sustainable society. The magnetic NIR activated Fe3 O4 @SiO2 /β-NaYF4 :Yb 3+, Tm 3+ /TiO2 (FS/UC/T) composites have been synthesized by using the solvothermal method by adding Fe3 O4 @SiO2 and Degussa P25 into the mixed solution of NaOH, ethanol, oleic acid, Re(NO3 )3 and NH4 F. Moreover, the obtained composites were explored for photocatalytic applications. It was found that FS/UC/T emit UV–vis light under irradiation of 980 nm laser and efficient energy transfer from β-NaYF4 :Yb 3+, Tm 3+ to TiO2 was verified. The photodegradation experiments for treating methylene blue (MB), rhodamine B (RhB), methyl orange (MO) and colorless phenol were carried out to evaluate the photocatalytic activities of the samples. The photodegradation rates reach 76.62%, 68.48%, 30.05% and 27.16% for MB, RhB, MO and phenol under irradiation of 980 nm laser, respectively, which suggested magnetic FS/UC/T composite is an advanced NIR-driven photocatalyst. Moreover, the magnetic photocatalyst showed easy separation and good stability in the recycled tests. It suggested a promising system to utilize the NIR energy for photocatalysis based on TiO2 and to utilize the magnetic for separation of photocatalysts, which will contribute to practical environmental remediation in the future.